Extracellular Alkaline Phosphatase from Mangrove Soil Yeast - Nur Hidayatul Alami; Windasari Putri Septarina; Tania Pratiwi; N. D Kuswytasari; Enny Zulaika; Maya Shovitri (LPPM, Institut Teknologi Sepuluh Nopember, 2019)
Alkaline phosphatase is a widely used enzyme in research and industry. Yeast is one of a microbial group that has the potency to produce alkaline phosphatase. This study aims to screen yeast from mangrove in Surabaya’s East Coast with the potential of alkaline phosphatase and to optimize the production of these enzymes. Screening test includes the measurement of phosphate solubilization index and concentration of soluble phosphate. Yeast with potential of phosphate solubilization will be used to measured the enzyme activity and also further optimized for extracellular alkaline phosphatase production. Optimization was done by determining the incubation time and a variety of combinations of phosphate source and temperature. The incubation time was adjusted to 7 days. Ca3(PO4)2 and KH2PO4 as the phosphate source and incubation temperature were adjusted to 29° C, 45° C, and 55° C. The results showed that isolates with the highest phosphate solubilization index were W1.1 and G3.2 (1.18 for W1.1 and 1.15 for G3.2). Yeast with the ability to solubilize phosphate was assumed to be Candida genus. W1.1 and G3.2 produced soluble phosphate in a concentration of 0.50 ppm and 0.77 ppm at the 7th day respectively. Candida G3.2 has higher enzyme activity than Candida W1.1. Candida G3.2 has optimal production for 3 days incubation time with a combination of temperature 29 °C and Ca3(PO4)2as the phosphate source which caused 97.8 U/mL enzyme activity.